2016
DOI: 10.1371/journal.pone.0161709
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Sectional Association between Diet Quality and Depressive Symptomology amongst Fijian Adolescents

Abstract: ObjectiveTo examine the relationship between diet quality and depressive symptomology amongst a community-based sample of Fijian adolescents.MethodsParticipants included 7,237 adolescents (52.6% girls; mean age 15.6 years) at baseline (2005) and 2,948 (56% girls; mean age 17.4 years) at follow-up (2007/2008), from the Pacific Obesity Prevention in Communities Project. Intervention schools (n = 7) were selected from Nasinu, near Suva on the main Fijian island Viti Levu, and comparison schools (n = 11) were chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…Prior cross-sectional studies are not wholly consistent. The majority of studies are in accordance with our findings (Appelhans et al, 2012;Beydoun et al, 2009;Jacka et al, 2010;Pagoto et al, 2009;Quirk et al, 2013;Rienks et al, 2013;Saneei et al, 2016;Sinclair et al, 2016), however, one study did not find an association when using the AHEI in a population of obese/overweigh African American women (Whitaker et al, 2014). A second study only found an association in distinct clinical subtypes based on a German guideline based diet score.…”
Section: Discussionsupporting
confidence: 89%
“…Prior cross-sectional studies are not wholly consistent. The majority of studies are in accordance with our findings (Appelhans et al, 2012;Beydoun et al, 2009;Jacka et al, 2010;Pagoto et al, 2009;Quirk et al, 2013;Rienks et al, 2013;Saneei et al, 2016;Sinclair et al, 2016), however, one study did not find an association when using the AHEI in a population of obese/overweigh African American women (Whitaker et al, 2014). A second study only found an association in distinct clinical subtypes based on a German guideline based diet score.…”
Section: Discussionsupporting
confidence: 89%
“…Increasingly, researchers are also recognizing the importance of diet in mental health. A “Western” diet high in fat and sugar has been linked to psychopathology in humans ( Jacka et al, 2010a , 2010b ; Sinclair et al, 2016 ). A diet rich in processed meats, sugary foods, and high-fat dairy products is associated with an increased risk for depression ( Akbaraly et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…This trend is consistent with findings from previous studies [ 77 , 86 ]. Additionally, the inverse link between exercise and mental distress was formerly described [ 38 , 77 ]; as well as the association between high fast-food consumption and mental distress in adolescents/young adults [ 77 , 87 ]. However, our current study is linking these significant variables to young men, as a specific sub-population to be at risk.…”
Section: Discussionmentioning
confidence: 99%